Church lists in Haskell - haskell

I had to implement the haskell map function to work with church lists which are defined as following:
type Churchlist t u = (t->u->u)->u->u
In lambda calculus, lists are encoded as following:
[] := λc. λn. n
[1,2,3] := λc. λn. c 1 (c 2 (c 3 n))
The sample solution of this exercise is:
mapChurch :: (t->s) -> (Churchlist t u) -> (Churchlist s u)
mapChurch f l = \c n -> l (c.f) n
I have NO idea how this solution works and I don't know how to create such a function. I have already experience with lambda calculus and church numerals, but this exercise has been a big headache for me and I have to be able to understand and solve such problems for my exam next week. Could someone please give me a good source where I could learn to solve such problems or give me a little guidance on how it works?

All lambda calculus data structures are, well, functions, because that's all there is in the lambda calculus. That means that the representation for a boolean, tuple, list, number, or anything, has to be some function that represents the active behavior of that thing.
For lists, it is a "fold". Immutable singly-linked lists are usually defined List a = Cons a (List a) | Nil, meaning the only ways you can construct a list is either Nil or Cons anElement anotherList. If you write it out in lisp-style, where c is Cons and n is Nil, then the list [1,2,3] looks like this:
(c 1 (c 2 (c 3 n)))
When you perform a fold over a list, you simply provide your own "Cons" and "Nil" to replace the list ones. In Haskell, the library function for this is foldr
foldr :: (a -> b -> b) -> b -> [a] -> b
Look familiar? Take out the [a] and you have the exact same type as Churchlist a b. Like I said, church encoding represents lists as their folding function.
So the example defines map. Notice how l is used as a function: it is the function that folds over some list, after all. \c n -> l (c.f) n basically says "replace every c with c . f and every n with n".
(c 1 (c 2 (c 3 n)))
-- replace `c` with `(c . f)`, and `n` with `n`
((c . f) 1 ((c . f) 2) ((c . f) 3 n)))
-- simplify `(foo . bar) baz` to `foo (bar baz)`
(c (f 1) (c (f 2) (c (f 3) n))
It should be apparent now that this is indeed a mapping function, because it looks just like the original, except 1 turned into (f 1), 2 to (f 2), and 3 to (f 3).

So let's start by encoding the two list constructors, using your example as reference:
[] := λc. λn. n
[1,2,3] := λc. λn. c 1 (c 2 (c 3 n))
[] is the end of list constructor, and we can lift that straight from the example. [] already has meaning in haskell, so let's call ours nil:
nil = \c n -> n
The other constructor we need takes an element and an existing list, and creates a new list. Canonically, this is called cons, with the definition:
cons x xs = \c n -> c x (xs c n)
We can check that this is consistent with the example above, since
cons 1 (cons 2 (cons 3 nil))) =
cons 1 (cons 2 (cons 3 (\c n -> n)) =
cons 1 (cons 2 (\c n -> c 3 ((\c' n' -> n') c n))) =
cons 1 (cons 2 (\c n -> c 3 n)) =
cons 1 (\c n -> c 2 ((\c' n' -> c' 3 n') c n) ) =
cons 1 (\c n -> c 2 (c 3 n)) =
\c n -> c 1 ((\c' n' -> c' 2 (c' 3 n')) c n) =
\c n -> c 1 (c 2 (c 3 n)) =
Now, consider the purpose of the map function - it is to apply the given function to each element of the list. So let's see how that works for each of the constructors.
nil has no elements, so mapChurch f nil should just be nil:
mapChurch f nil
= \c n -> nil (c.f) n
= \c n -> (\c' n' -> n') (c.f) n
= \c n -> n
= nil
cons has an element and a rest of list, so, in order for mapChurch f to work propery, it must apply f to the element and mapChurch f to rest of the list. That is, mapChurch f (cons x xs) should be the same as cons (f x) (mapChurch f xs).
mapChurch f (cons x xs)
= \c n -> (cons x xs) (c.f) n
= \c n -> (\c' n' -> c' x (xs c' n')) (c.f) n
= \c n -> (c.f) x (xs (c.f) n)
-- (c.f) x = c (f x) by definition of (.)
= \c n -> c (f x) (xs (c.f) n)
= \c n -> c (f x) ((\c' n' -> xs (c'.f) n') c n)
= \c n -> c (f x) ((mapChurch f xs) c n)
= cons (f x) (mapChurch f xs)
So since all lists are made from those two constructors, and mapChurch works on both of them as expected, mapChurch must work as expected on all lists.

Well, we can comment the Churchlist type this way to clarify it:
-- Tell me...
type Churchlist t u = (t -> u -> u) -- ...how to handle a pair
-> u -- ...and how to handle an empty list
-> u -- ...and then I'll transform a list into
-- the type you want
Note that this is intimately related to the foldr function:
foldr :: (t -> u -> u) -> u -> [t] -> u
foldr k z [] = z
foldr k z (x:xs) = k x (foldr k z xs)
foldr is a very general function that can implement all sorts of other list functions. A trivial example that will help you is implementing a list copy with foldr:
copyList :: [t] -> [t]
copyList xs = foldr (:) [] xs
Using the commented type above, foldr (:) [] means this: "if you see an empty list return the empty list, and if you see a pair return head:tailResult."
Using Churchlist, you can easily write the counterpart this way:
-- Note that the definitions of nil and cons mirror the two foldr equations!
nil :: Churchlist t u
nil = \k z -> z
cons :: t -> Churchlist t u -> Churchlist t u
cons x xs = \k z -> k x (xs k z)
copyChurchlist :: ChurchList t u -> Churchlist t u
copyChurchlist xs = xs cons nil
Now, to implement map, you just need to replace cons with a suitable function, like this:
map :: (a -> b) -> [a] -> [b]
map f xs = foldr (\x xs' -> f x:xs') [] xs
Mapping is like copying a list, except that instead of just copying the elements verbatim you apply f to each of them.
Study all of this carefully, and you should be able to write mapChurchlist :: (t -> t') -> Churchlist t u -> Churchlist t' u on your own.
Extra exercise (easy): write these list functions in terms of foldr, and write counterparts for Churchlist:
filter :: (a -> Bool) -> [a] -> [a]
append :: [a] -> [a] -> [a]
-- Return first element of list that satisfies predicate, or Nothing
find :: (a -> Bool) -> [a] -> Maybe a
If you're feeling like tackling something harder, try writing tail for Churchlist. (Start by writing tail for [a] using foldr.)

Related

Haskell dependent, independent variables in lambda function as applied to foldr

Given
> foldr (+) 5 [1,2,3,4]
15
this second version
foldr (\x n -> x + n) 5 [1,2,3,4]
also returns 15. The first thing I don't understand about the second version is how foldr knows which variable is associated with the accumulator-seed 5 and which with the list variable's elements [1,2,3,4]. In the lambda calculus way, x would seem to be the dependent variable and n the independent variable. So if this
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr _ z [] = z
foldr f z (x:xs) = f x (foldr f z xs)
is foldr and these
:type foldr
foldr :: Foldable t => (a -> b -> b) -> b -> t a -> b
:t +d foldr
foldr :: (a -> b -> b) -> b -> [a] -> b
its type declarations, can I glean, deduce the answer to "which is dependent and which is independent" from the type declaration itself? It would seem both examples of foldr above must be doing this
(+) 1 ((+) 2 ((+) 3 ((+) 4 ((+) 5 0))))
I simply guessed the second, lambda function version above, but I don't really understand how it works, whereas the first version with (+) breaks down as shown directly above.
Another example would be this
length' = foldr (const (1+)) 0
where, again, const seems to know to "throw out" the incoming list elements and simply increment, starting with the initial accumulator value. This is the same as
length' = foldr (\_ acc -> 1 + acc) 0
where, again, Haskell knows which of foldr's second and third arguments -- accumulator and list -- to treat as the dependent and independent variable, seemingly by magic. But no, I'm sure the answer lies in the type declaration (which I can't decipher, hence, this post), as well as the lore of lambda calculus, of which I'm a beginner.
Update
I've found this
reverse = foldl (flip (:)) []
and then applying to a list
foldl (flip (:)) [] [1,2,3]
foldl (flip (:)) (1:[]) [2,3]
foldl (flip (:)) (2:1:[]) [3]
foldl (flip (:)) (3:2:1:[]) []
. . .
Here it's obvious that the order is "accumulator" and then list, and flip is flipping the first and second variables, then subjecting them to (:). Again, this
reverse = foldl (\acc x -> x : acc) []
foldl (\acc x -> x : acc) [] [1,2,3]
foldl (\acc x -> x : acc) (1:[]) [1,2,3]
. . .
seems also to rely on order, but in the example from further above
length' = foldr (\_ acc -> 1 + acc) 0
foldr (\_ acc -> 1 + acc) 0 [1,2,3]
how does it know 0 is the accumulator and is bound to acc and not the first (ghost) variable? So as I understand (the first five pages of) lambda calculus, any variable that is "lambda'd," e.g., \x is a dependent variable, and all other non-lambda'd variables are independent. Above, the \_ is associated with [1,2,3] and the acc, ostensibly the independent variable, is 0; hence, order is not dictating assignment. It's as if acc was some keyword that when used always binds to the accumulator, while x is always talking about the incoming list members.
Also, what is the "algebra" in the type definition where t a is transformed to [a]? Is this something from category theory? I see
Data.Foldable.toList :: t a -> [a]
in the Foldable definition. Is that all it is?
By "dependent" you most probably mean bound variable.
By "independent" you most probably mean free (i.e. not bound) variable.
There are no free variables in (\x n -> x + n). Both x and n appear to the left of the arrow, ->, so they are named parameters of this lambda function, bound inside its body, to the right of the arrow. Being bound means that each reference to n, say, in the function's body is replaced with the reference to the corresponding argument when this lambda function is indeed applied to its argument(s).
Similarly both _ and acc are bound in (\_ acc -> 1 + acc)'s body. The fact that the wildcard is used here, is immaterial. We could just have written _we_dont_care_ all the same.
The parameters in lambda function definition get "assigned" (also called "bound") the values of the arguments in an application, purely positionally. The first argument will be bound / assigned to the first parameter, the second argument - to the second parameter. Then the lambda function's body will be entered and further reduced according to the rules.
This can be seen a bit differently stating that actually in lambda calculus all functions have only one parameter, and multi-parameter functions are actually nested uni-parameter lambda functions; and that the application is left-associative i.e. nested to the left.
What this actually means is quite simply
(\ x n -> x + n) 5 0
=
(\ x -> (\ n -> x + n)) 5 0
=
((\ x -> (\ n -> x + n)) 5) 0
=
(\ n -> 5 + n) 0
=
5 + 0
As to how Haskell knows which is which from the type signatures, again, the type variables in the functional types are also positional, with first type variable corresponding to the type of the first expected argument, the second type variable to the second expected argument's type, and so on.
It is all purely positional.
Thus, as a matter of purely mechanical and careful substitution, since by the definition of foldr it holds that foldr g 0 [1,2,3] = g 1 (foldr g 0 [2,3]) = ... = g 1 (g 2 (g 3 0)), we have
foldr (\x n -> x + n) 0 [1,2,3]
=
(\x n -> x + n) 1 ( (\x n -> x + n) 2 ( (\x n -> x + n) 3 0 ))
=
(\x -> (\n -> x + n)) 1 ( (\x n -> x + n) 2 ( (\x n -> x + n) 3 0 ))
=
(\n -> 1 + n) ( (\x n -> x + n) 2 ( (\x n -> x + n) 3 0 ))
=
1 + ( (\x n -> x + n) 2 ( (\x n -> x + n) 3 0 ))
=
1 + ( (\x (\n -> x + n)) 2 ( (\x n -> x + n) 3 0 ))
=
1 + (\n -> 2 + n) ( (\x n -> x + n) 3 0 )
=
1 + (2 + (\x n -> x + n) 3 0 )
=
1 + (2 + (\x -> (\n -> x + n)) 3 0 )
=
1 + (2 + (\n -> 3 + n) 0 )
=
1 + (2 + ( 3 + 0))
In other words, there is absolutely no difference between (\x n -> x + n) and (+).
As for that t in foldr :: Foldable t => (a -> b -> b) -> b -> t a -> b, what that means is that given a certain type T a, if instance Foldable T exists, then the type becomes foldr :: (a -> b -> b) -> b -> T a -> b, when it's used with a value of type T a.
One example is Maybe a and thus foldr (g :: a -> b -> b) (z :: b) :: Maybe a -> b.
Another example is [] a and thus foldr (g :: a -> b -> b) (z :: b) :: [a] -> b.
(edit:) So let's focus on lists. What does it mean for a function foo to have that type,
foo :: (a -> b -> b) -> b -> [a] -> b
? It means that it expects an argument of type a -> b -> b, i.e. a function, let's call it g, so that
foo :: (a -> b -> b) -> b -> [a] -> b
g :: a -> b -> b
-------------------------------------
foo g :: b -> [a] -> b
which is itself a function, expecting of some argument z of type b, so that
foo :: (a -> b -> b) -> b -> [a] -> b
g :: a -> b -> b
z :: b
-------------------------------------
foo g z :: [a] -> b
which is itself a function, expecting of some argument xs of type [a], so that
foo :: (a -> b -> b) -> b -> [a] -> b
g :: a -> b -> b
z :: b
xs :: [a]
-------------------------------------
foo g z xs :: b
And what could such function foo g z do, given a list, say, [x] (i.e. x :: a, [x] :: [a])?
foo g z [x] = b where
We need to produce a b value, but how? Well, g :: a -> b -> b produces a function b -> b given an value of type a. Wait, we have that!
f = g x -- f :: b -> b
and what does it help us? Well, we have z :: b, so
b = f z
And what if it's [] we're given? We don't have any as then at all, but we have a b type value, z -- so instead of the above we'd just define
b = z
And what if it's [x,y] we're given? We'll do the same f-building trick, twice:
f1 = g x -- f1 :: b -> b
f2 = g y -- f2 :: b -> b
and to produce b we have many options now: it's z! or maybe, it's f1 z!? or f2 z? But the most general thing we can do, making use of all the data we have access to, is
b = f1 (f2 z)
for a right-fold (...... or,
b = f2 (f1 z)
for a left).
And if we substitute and simplify, we get
foldr g z [] = z
foldr g z [x] = g x z -- = g x (foldr g z [])
foldr g z [x,y] = g x (g y z) -- = g x (foldr g z [y])
foldr g z [x,y,w] = g x (g y (g w z)) -- = g x (foldr g z [y,w])
A pattern emerges.
Etc., etc., etc.
A sidenote: b is a bad naming choice, as is usual in Haskell. r would be much much better -- a mnemonic for "recursive result".
Another mnemonic is the order of g's arguments: a -> r -> r suggests, nay dictates, that a list's element a comes as a first argument; r the recursive result comes second (the Result of Recursively processing the Rest of the input list -- recursively, thus in the same manner); and the overall result is then produced by this "step"-function, g.
And that's the essence of recursion: recursively process self-similar sub-part(s) of the input structure, and complete the processing by a simple single step:
a a
: `g`
[a] r
------------- -------------
[a] r
[a]
a [a]
--------
(x : xs) -> r
xs -> r
----------------------
( x , r ) -> r --- or, equivalently, x -> r -> r
Well, the foldr itself knows this by definition. It was defined in such way that its function argument accepts the accumulator as 2nd argument.
Just like when you write a div x y = ... function you are free to use y as dividend.
Maybe you got confused by the fact that foldr and foldl has swapped arguments in the accumulator funtions?
As Steven Leiva says here, a foldr (1) takes a list and replaces the cons operators (:) with the given function and (2) replaces the last empty list [] with the accumulator-seed, which is what the definition of foldr says it will do
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr _ z [] = z
foldr f z (x:xs) = f x (foldr f z xs)
So de-sugared [1,2,3] is
(:) 1 ((:) 2 ((:) 3 []))
and the recursion is in effect replacing the (:) with f, and as we see in foldr f z (x:xs) = f x (foldr f z xs), the z seed value is going along for the ride until the base case where it is substituted for the [], fulfilling (1) and (2) above.
My first confusion was seeing this
foldr (\x n -> x + n) 0 [1,2,3]
and not understanding it would be expanded out, per definition above, to
(\x n -> x + n) 1 ((\x n -> x + n) 2 ((\x n -> x + n) 3 0 ))
Next, due to a weak understanding of how the actual beta reduction would progress, I didn't understand the second-to-third step below
(\x -> (\n -> x + n)) 1 ...
(\n -> 1 + n) ...
1 + ...
That second-to-third step is lambda calculus being bizarre all right, but is at the root of why (+) and (\x n -> x + n) are the same thing. I don't think it's pure lambda calculus addition, but it (verbosely) mimics addition in recursion. I probably need to jump back into lambda calculus to really grasp why (\n -> 1 + n) turns into 1 +
My worse mental block was thinking I was looking at some sort of eager evaluation inside the parentheses first
foldr ((\x n -> x + n) 0 [1,2,3,4])
where the three arguments to foldr would interact first, i.e., 0 would be bound to the x and the list member to the n
(\x n -> x + n) 0 [1,2,3,4]
0 + 1
. . . then I didn't know what to think. Totally wrong-headed, even though, as Will Ness points out above, beta reduction is positional in binding arguments to variables. But, of course, I left out the fact that Haskell currying means we follow the expansion of foldr first.
I still don't fully understand the type definition
foldr :: (a -> b -> b) -> b -> [a] -> b
other than to comment/guess that the first a and the [a] mean a is of the type of the members of the incoming list and that the (a -> b -> b) is a prelim-microcosm of what foldr will do, i.e., it will take an argument of the incoming list's type (in our case the elements of the list?) then another object of type b and produce an object b. So the seed argument is of type b and the whole process will finally produce something of type b, also the given function argument will take an a and ultimately give back an object b which actually might be of type a as well, and in fact is in the above example with integers... IOW, I don't really have a firm grasp of the type definition...

foldr with 4 arguments?

I am struggling to understand why this code taken from the haskell.org exercise page typechecks (and works as a list reversal function):
myReverse :: [a] -> [a]
myReverse xs = foldr (\x fId empty -> fId (x : empty)) id xs []
My first point of confusion is that foldr accepts 3 arguments, not 4 :
foldr :: Foldable t => (a -> b -> b) -> b -> t a -> b
so I am guessing that myReverse is equivalent to:
myReverse xs = foldr ((\x fId empty -> fId (x : empty)) id) xs []
but then this should not work either since in the lambda, x is a list element rather than a function ...
Think of it this way. Every function accepts exactly one argument. It may return another function (that accepts one argument). The thing that looks like a multi-argument call
f a b c
is actually parsed as
((f a) b) c
that is, a chain of single-argument function applications. A function type
f :: a -> b -> c -> d
can be decomposed to
f :: a -> (b -> (c -> d))
i.e. a function returning a function returning a function. We usually regard it as a function of three arguments. But can it accept more than three? Yes, if d happens to be another function type.
This is exactly what happens with your fold example. The function that you pass as the first argument to foldr accepts three arguments, which is exactly the same as accepting two arguments and returning another function. Now the (simplified) type of foldr is
(a -> b -> b) -> b -> [a] -> b
but if you look at the first argument of it, you see it's a function of three arguments. Which is, as we have seen, exactly the same as a function that acceora two arguments and returns a function. So the b happens to be a function type. Since b is also the the return tuoe of foldr when applied to three arguments
foldr (\x fId empty -> fId (x : empty)) id
and it's a function, it can now be applied to another argument
(foldr (\x fId empty -> fId (x : empty)) id xs) []
I let you figure out what b actually is.
First of all the variables naming is atrocious. I always use r for the second argument to a foldr's reducer function, as a mnemonic for the "recursive result". "empty" is too overloaded with meaning; it is better to use some neutral name so it is easier to see what it is without any preconceived notions:
myReverse :: [a] -> [a]
myReverse xs = foldr (\x r n -> r (x : n)) id xs []
By virtue of foldr's definition,
foldr f z (x:xs) === f x (foldr f z xs)
i.e.
myReverse [a,b,c,...,z]
= foldr (\x r n -> r (x : n)) id [a,b,c,...,z] []
= (\x r n -> r (x : n)) a (foldr (\x r n -> r (x : n)) id [b,c,...,z]) []
= (\x r n -> r (x : n))
a
(foldr (\x r n -> r (x : n)) id [b,c,...,z])
[]
= let { x = a
; r = foldr (\x r n -> r (x : n)) id [b,c,...,z]
; n = []
}
in r (x : n)
= foldr (\x r n -> r (x : n)) id [b,c,...,z] (a : [])
= foldr (\x r n -> r (x : n)) id [b,c,...,z] [a]
= ....
= foldr (\x r n -> r (x : n)) id [c,...,z] (b : [a])
= foldr (\x r n -> r (x : n)) id [c,...,z] [b,a]
= ....
= foldr (\x r n -> r (x : n)) id [] [z,...,c,b,a]
= id [z,...,c,b,a]
I hope this illustration makes it clearer what is going on there. The extra argument is expected by the reducer function, which is pushed into action by foldr ... resulting in the operational equivalent of
= foldl (\n x -> (x : n)) [] [a,b,c,...,z]
As it turns out, myReverse implementation is using the equivalence
foldl (flip f) n xs === foldr (\x r -> r . f x) id xs n

Recursion scheme in Haskell for repeatedly breaking datatypes into "head" and "tail" and yielding a structure of results

In Haskell, I recently found the following function useful:
listCase :: (a -> [a] -> b) -> [a] -> [b]
listCase f [] = []
listCase f (x:xs) = f x xs : listCase f xs
I used it to generate sliding windows of size 3 from a list, like this:
*Main> listCase (\_ -> take 3) [1..5]
[[2,3,4],[3,4,5],[4,5],[5],[]]
Is there a more general recursion scheme which captures this pattern? More specifically, that allows you to generate a some structure of results by repeatedly breaking data into a "head" and "tail"?
What you are asking for is a comonad. This may sound scarier than monad, but is a simpler concept (YMMV).
Comonads are Functors with additional structure:
class Functor w => Comonad w where
extract :: w a -> a
duplicate :: w a -> w (w a)
extend :: (w a -> b) -> w a -> w b
(extendand duplicate can be defined in terms of each other)
and laws similar to the monad laws:
duplicate . extract = id
duplicate . fmap extract = id
duplicate . duplicate = fmap duplicate . duplicate
Specifically, the signature (a -> [a] -> b) takes non-empty Lists of type a. The usual type [a] is not an instance of a comonad, but the non-empty lists are:
data NE a = T a | a :. NE a deriving Functor
instance Comonad NE where
extract (T x) = x
extract (x :. _) = x
duplicate z#(T _) = T z
duplicate z#(_ :. xs) = z :. duplicate xs
The comonad laws allow only this instance for non-empty lists (actually a second one).
Your function then becomes
extend (take 3 . drop 1 . toList)
Where toList :: NE a -> [a] is obvious.
This is worse than the original, but extend can be written as =>> which is simpler if applied repeatedly.
For further information, you may start at What is the Comonad typeclass in Haskell?.
This looks like a special case of a (jargon here but it can help with googling) paramorphism, a generalisation of primitive recursion to all initial algebras.
Reimplementing ListCase
Let's have a look at how to reimplement your function using such a combinator. First we define the notion of paramorphism: a recursion principle where not only the result of the recursive call is available but also the entire substructure this call was performed on:
The type of paraList tells me that in the (:) case, I will have access to the head, the tail and the value of the recursive call on the tail and that I need to provide a value for the base case.
module ListCase where
paraList :: (a -> [a] -> b -> b) -- cons
-> b -- nil
-> [a] -> b -- resulting function on lists
paraList c n [] = n
paraList c n (x : xs) = c x xs $ paraList c n xs
We can now give an alternative definition of listCase:
listCase' :: (a -> [a] -> b) -> [a] -> [b]
listCase' c = paraList (\ x xs tl -> c x xs : tl) []
Considering the general case
In the general case, we are interested in building a definition of paramorphism for all data structures defined as the fixpoint of a (strictly positive) functor. We use the traditional fixpoint operator:
newtype Fix f = Fix { unFix :: f (Fix f) }
This builds an inductive structure layer by layer. The layers have an f shape which maybe better grasped by recalling the definition of List using this formalism. A layer is either Nothing (we're done!) or Just (head, tail):
newtype ListF a as = ListF { unListF :: Maybe (a, as) }
type List a = Fix (ListF a)
nil :: List a
nil = Fix $ ListF $ Nothing
cons :: a -> List a -> List a
cons = curry $ Fix . ListF .Just
Now that we have this general framework, we can define para generically for all Fix f where f is a functor:
para :: Functor f => (f (Fix f, b) -> b) -> Fix f -> b
para alg = alg . fmap (\ rec -> (rec, para alg rec)) . unFix
Of course, ListF a is a functor. Meaning we could use para to reimplement paraList and listCase.
instance Functor (ListF a) where fmap f = ListF . fmap (fmap f) . unListF
paraList' :: (a -> List a -> b -> b) -> b -> List a -> b
paraList' c n = para $ maybe n (\ (a, (as, b)) -> c a as b) . unListF
listCase'' :: (a -> List a -> b) -> List a -> List b
listCase'' c = paraList' (\ x xs tl -> cons (c x xs) tl) nil
You can implement a simple bijection toList, fromList to test it if you want. I could not be bothered to reimplement take so it's pretty ugly:
toList :: [a] -> List a
toList = foldr cons nil
fromList :: List a -> [a]
fromList = paraList' (\ x _ tl -> x : tl) []
*ListCase> fmap fromList . fromList . listCase'' (\ _ as -> toList $ take 3 $ fromList as). toList $ [1..5]
[[2,3,4],[3,4,5],[4,5],[5],[]]

Can mapEvery be implemented with foldr

For a function that maps a function to every nth element in a list:
mapEvery :: Int -> (a -> a) -> [a] -> [a]
mapEvery n f = zipWith ($) (drop 1 . cycle . take n $ f : repeat id)
Is it possible to implement this with foldr like ordinary map?
EDIT: In the title, changed 'folder' to 'foldr'. Autocorrect...
Here's one solution
mapEvery :: Int -> (a -> a) -> [a] -> [a]
mapEvery n f as = foldr go (const []) as 1 where
go a as m
| m == n = f a : as 1
| otherwise = a : as (m+1)
This uses the "foldl as foldr" trick to pass state from the left to the right along the list as you fold. Essentially, if we read the type of foldr as (a -> r -> r) -> r -> [a] -> r then we instantiate r as Int -> [a] where the passed integer is the current number of elements we've passed without calling the function.
Yes, it can:
mapEvery :: Int -> (a -> a) -> [a] -> [a]
mapEvery n f xs
= foldr (\y ys -> g y : ys) []
$ zip [1..] xs
where
g (i, y) = if i `mod` n == 0 then f y else y
And since it's possible to implement zip in terms of foldr, you could get even more fold-y if you really wanted. This even works on infinite lists:
> take 20 $ mapEvery 5 (+1) $ repeat 1
[1,1,1,1,2,1,1,1,1,2,1,1,1,1,2,1,1,1,1,2]
This is what it looks like with even more foldr and inlining g:
mapEvery :: Int -> (a -> a) -> [a] -> [a]
mapEvery _ _ [] = []
mapEvery n f xs
= foldr (\(i, y) ys -> (if i `mod` n == 0 then f y else y) : ys) []
$ foldr step (const []) [1..] xs
where
step _ _ [] = []
step x zipsfn (y:ys) = (x, y) : zipsfn ys
Now, would I recommend writing it this way? Absolutely not. This is about as obfuscated as you can get while still writing "readable" code. But it does demonstrate that this is possible to use the very powerful foldr to implement relatively complex functions.

Haskell: List Comprehensions and higher-order functions

I've tried to transform the following list comprehension:
f xs = [ x+8 | (x,_) <- xs ]
using higher-order functions.
My first solution was:
f' xs = map (\(x,_) -> x+8) xs
After I tried various other approaches, I found out that the following also works:
f' xs = map((+8).fst) xs
Both versions of f' give the same (correct) output, but I don't understand why (+8).fst is equal to \(x,_) -> x+8 when using map on a list of tuples.
The definition of fst is
fst :: (a, b) -> a
fst (a, _) = a
and the definition of (.) is
(.) :: (b -> c) -> (a -> b) -> a -> c
(f . g) = \x -> f (g x)
If we use these definitions to expand your function, we get
f' xs = map ((+8) . fst) xs
f' xs = map (\x -> (+8) (fst x)) xs -- definition of (.)
f' xs = map (\x -> (+8) ((\(a, _) -> a) x)) -- definition of fst
f' xs = map (\(a, _) -> (+8) a) -- we can move the pattern matching
f' xs = map (\(a, _) -> a + 8) -- expand section
Both versions of f' give the same (correct) output, but I don't understand why (+8).fst is equal to (x,_) -> x+8 when using map on a list of tuples.
The type of fst is:
fst :: (a, b) -> a
and what it does is it takes the first element of a pair (a tuple of two elements).
The type of (+8) is:
(+8) :: Num a => a -> a
and what it does is it takes as input a Num, applies + 8 to it and returns the result.
Now, the type of (+8) . fst is:
((+8).fst) :: Num c => (c, b) -> c
which is the composition of fst and (+8). Specifically it's the function that takes as input a pair, extracts the first element and adds 8 to it.
This can be easily seen by seen an example:
((+8).fst) (3, 'a')
-- 11
The same thing happens with \ (x, _) -> x + 8. You take a pair as input (in the lambda), pattern match the first argument to x, increment it by 8 and return it:
(\ (x, _) -> x + 8) (3, 'a')
-- 11

Resources